Commentary: Inquiry-Creative Learning as a Pedagogical Bridge between Ethnoscience and Critical Thinking in Science Teacher Education - Verawati, Ni Nyoman Sri Putu; Wahyudi, Wahyudi (Multi Discere Journal, 2026)
Ethnoscience has gained increasing attention in science education because it connects scientific concepts with local wisdom, cultural practices, and learners’ lived experiences. However, the inclusion of cultural contexts in science learning does not automatically lead to the development of critical thinking. This commentary discusses the integration of ethnoscience into Inquiry-Creative Learning as a pedagogical approach for strengthening the critical thinking skills of prospective science teachers. It argues that ethnoscience can be transformed from a contextual learning resource into a structured pedagogical experience when it is mediated through inquiry, creativity, evidence evaluation, and scientific reasoning. Inquiry-Creative Learning functions as a pedagogical bridge between ethnoscience and critical thinking because it enables prospective science teachers to identify culturally grounded scientific problems, generate hypotheses, design creative investigations, evaluate evidence, and communicate reasoned conclusions. At the same time, this commentary cautions against treating ethnoscience merely as a cultural illustration or assuming that local wisdom automatically promotes critical thinking. The article highlights the need for stronger conceptual framing, authentic assessment, and teacher education curricula that prepare prospective science teachers to integrate ethnoscience through inquiry, creativity, and evidence-based reasoning.